Penyuluhan Pembuatan Pupuk Bokashi dari Kotoran Ayam dan Abu Sekam di Nagari Mungka - Trisna Kumala Sari; Riga Riga; Isra Yeni; Syamsi Aini; Desy Kurniawati; Romy Dwipa Yamesa Away; Melindra Mulia (Universitas Mathla'ul Anwar Banten, 2022)
COUNSELING ON MAKING BOKASHI FERTILIZER FROM CHICKEN MANURE AND HUSK ASH IN NAGARI MUNGKA. Community activities in the field of livestock are growing in Nagari Mungka, especially raising chickens. However, the processing of chicken manure waste is not handled properly. This may be due to the lack of public knowledge about this waste processing technique. This counseling aims to improve the knowledge and skills of chicken farmers in making bokashi fertilizer from chicken feces in Nagari Mungka, Lima Puluh Kota District. Bokashi fertilizer is a type of organic fertilizer that uses decomposers in the manufacturing process. The basic ingredients for this bokashi fertilizer are chicken feces, husk ash, bran and EM4. The counseling activity includes presentation of material, demonstration and evaluation of activity. Chicken farmers receive the knowledge about the benefits of bokashi fertilizer, how to make it and how to market it if it has the potential to be sold. This activity has a great influence on chicken farmers because this activity is very useful and right on target. Chicken farmers look enthusiastic in participating in the activities. The result of this community service activity is the increased knowledge and skills of breeders in processing chicken manure into bokashi fertilizer and have the desire to try and apply it.